Transport in multilayered nanostructures:the dynamical mean-field theory approach - Freericks James K (World Scientific, 2006)
This novel book is the first comprehensive text on dynamical mean-field theory (DMFT), which has emerged over the past two decades as one of the most powerful new developments in many-body physics. Written by one of the key researchers in the field, the volume develops the formalism of many-body Green's functions using the equation of motion approach, which requires an undergraduate solid state physics course and a graduate quantum mechanics course as prerequisites. The DMFT is applied to study transport in multilayered nanostructures, which is likely to be one of the most prominent applications of nanotechnology in the coming years. The text is modern in scope focusing on exact numerical methods rather than the perturbation theory. Formalism is developed first for the bulk and then for the inhomogeneous multilayered systems. The science behind the metal-insulator transition, electronic
Keywords: Thin films, Multilayered --Mathematics; Many-body problem; Mean field theory; Nanostructures --Mathematics